Highly efficient azido-Ugi multicomponent reactions for the synthesis of bioactive tetrazoles bearing sulfonamide scaffolds. (2nd July 2021) - Nazeri, Mohammad Taghi; Nowee, Ali Beygzade; Javanbakht, Siamak; Farhid, Hassan; Shaabani, Ahmad; Notash, Behrouz
Abstract: Recent studies revealed that the contribution of the different bioactive scaffolds in one structure creates modern drugs/compounds with unique synergistic biological properties. In this regard, thanks to the interesting biological and medicinal properties of sulfonamide and tetrazole skeletons, this study describes the engagement of sulfonamides in the Ugi tetrazole reaction to access a library of tetrazole bearing sulfonamide. This four-component reaction was performed in a one-pot among available starting material, i.e., an isocyanide, a sulfonamide, an aldehyde and sodium azide in MeOH at 45 °C using ZnCl2 as a catalyst, for the synthesis of very versatile products with high atom economy and yields. The key point in this strategy is the formation of an intermediate Schiff base and its activation in the azido-Ugi reaction by a Lewis acid catalyst. Importantly, all products are purified through the group-assisted purification (GAP) chemistry, which can avoid traditional purification such as recrystallization and chromatography methods. Also, the docking study between the synthesized compounds and human serum albumin (HSA) was stimulated to theoretically rationalize their biological activity and potential binding interactions. Graphical abstract: Image 1